Local Exposure to School Shootings and Youth Antidepressant Use - Maya Rossin-Slater; Molly Schnell; Hannes Schwandt; Sam Trejo; Lindsey Uniat (Institute of Labor Economics (IZA), 2019)
While over 240,000 American students experienced a school shooting in the last two decades, little is known about the impacts of these events on the mental health of surviving youth. Using large-scale prescription data from 2006 to 2015, we examine the effects of 44 school shootings on youth antidepressant use in a difference-in-difference framework. We find that local exposure to fatal school shootings increases youth antidepressant use by 21.4 percent in the following two years. These effects are smaller in areas with a higher density of mental health providers who focus on behavioral, rather than pharmacological, interventions.
Keywords: I18; J13; 330; school shootings; youth mental health; antidepressants